HIV-1 Gag trafficking. (November 2007) - Joshi, Anjali; Freed, Eric O
The process of HIV-1 assembly and release, which occurs largely at the plasma membrane, is driven by the Gag precursor protein, Pr55Gag. Because Gag plays a central role in orchestrating the late stages of the virus replication cycle, elucidating the molecular mechanism by which Gag traffics to the site of virus assembly and defining the cellular machinery that regulates Gag localization are crucial to understanding HIV-1 replication. Ultimately, this information will be vital to devising effective approaches to controlling this pathogen. Numerous studies in recent years have provided new insights into both the viral and cellular determinants of HIV-1 Gag trafficking. The matrix domain of Gag plays an important role in directing Gag to the plasma membrane, in part by directly interacting with a specific phosphoinositide. Several cellular proteins have also been reported to function in Gag trafficking pathways. Current efforts in the field are directed toward understanding how these factors function in promoting Gag transport and virus assembly.